THE CLEYNESS OF ROCKS KARTAMISHS SEDIMENTARY COMPLEX OF KOBZIVSKE DEPOSIT AND ITS INFLUENCE ON RESERVOIRS PROPERTIES - Kurgansky, V.; Kolisnichenko, V.; Malyar, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of laboratory investigation the core and well logging influence of clayness is probed on lauter-capacity properties of rocks kartamishs sedimentary complex Kobzivske deposit. The models of type "Core-Log" for establishment of value clayness after the method Gamma Ray the investigation deposits are described. The proper conclusions to correlation connections between capacity properties and parameters of clayness reservoirs rocks kartamishs sedimentary complex of Kobzivske deposit are done.